Initiation of pharmacological therapy in Parkinson's disease: when, why, and how - de Bie, Rob M A; Clarke, Carl E; Espay, Alberto J; Fox, Susan H; Lang, Anthony E (Lancet neurology, 2020)
Debate is ongoing regarding when, why, and how to initiate pharmacotherapy for Parkinson's disease. Early initiation of dopaminergic therapies does not convey disease-modifying effects but does reduce disability. Concerns about the development of motor complications arising from the early initiation of levodopa, which led to misconceived levodopa-sparing strategies, have been largely mitigated by the outcomes of the PD MED and Levodopa in Early Parkinson's Disease (LEAP) studies. The LEAP study also showed the potential for early improvement in quality of life, even when disability is negligible. Until more effective methods of providing stable dopamine concentrations are developed, current evidence supports the use of levodopa as initial symptomatic treatment in most patients with Parkinson's disease, starting with low doses and titrating to therapeutic threshold. Monoamine oxidase-B inhibitors and dopamine agonists can be reserved as potential adjunct treatments later in the disease course. Future research will need to establish effective disease-modifying treatments, address whether patients’ quality of life is substantially improved with early initiation of treatment rather than a wait and watch strategy, and establish whether new levodopa formulations will delay onset of dyskinesia.